Oxford reading tree: six in a bed - Hunt, Roderick; Brychta, Alex (Oxford University Press China, 2012)
The Oxford Reading Tree is a widely used reading scheme for young learners. It features engaging stories and characters, such as Biff, Chip, and Kipper, designed to help children develop their reading skills. The scheme is structured in stages, gradually increasing in complexity to support children from early phonics to more advanced reading comprehension. It aims to foster a love of reading in children.